Physiologically‐Based Pharmacokinetic Modeling of Atorvastatin Incorporating Delayed Gastric Emptying and Acid‐to‐Lactone Conversion. (1st August 2019) - Morse, Bridget L.; Alberts, Jeffrey J.; Posada, Maria M.; Rehmel, Jessica; Kolur, Anil; Tham, Lai San; Loghin, Corina; Hillgren, Kathleen M.; Hall, Stephen D.; Dickinson, Gemma L.
Abstract : The drug–drug interaction profile of atorvastatin confirms that disposition is determined by cytochrome P450 (CYP) 3A4 and organic anion transporting polypeptides (OATPs). Drugs that affect gastric emptying, including dulaglutide, also affect atorvastatin pharmacokinetics (PK). Atorvastatin is a carboxylic acid that exists in equilibrium with a lactone form in vivo . The purpose of this work was to assess gastric acid–mediated lactone equilibration of atorvastatin and incorporate this into a physiologically‐based PK (PBPK) model to describe atorvastatin acid, lactone, and their major metabolites. In vitro acid‐to‐lactone conversion was assessed in simulated gastric fluid and included in the model. The PBPK model was verified with in vivo data including CYP3A4 and OATP inhibition studies. Altering the gastric acid–lactone equilibrium reproduced the change in atorvastatin PK observed with dulaglutide. The model emphasizes the need to include gastric acid–lactone conversion and all major atorvastatin‐related species for the prediction of atorvastatin PK.